The Tradition of Reciting Al-Fatihah as Healing at Al-Banat Gondang - Aftonur Rosyad; Moh Yusron Karimul Amin (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2023)
The tradition of reciting Al-Fatihah as a form of healing has become an integral part of culture and religious practice in various Islamic boarding schools in Indonesia. This article aims to explain and analyze this phenomenon by focusing on the al Banat Gondang Islamic boarding school as a center for Islamic religious learning and religious practices. As society's interest in alternative medicine and spirituality increases, these practices are gaining further attention. This article is based on field research and interviews with Islamic boarding school leaders, Islamic boarding school students, and individuals involved in these practices. The tradition of reading Al-Fatihah as a form of treatment at the al Banat Gondang Islamic boarding school developed as a result of the interpretation of the Islamic religion and local cultural heritage. This practice often includes certain rituals, such as reciting verses from the qur’an and special prayers, which are believed to have healing effects. In many cases, reciting Al-Fatihah is used as an effort to overcome physical and mental health problems, and also as a means to improve spirituality.